THU0084 Histone deacetylase 1 (HDAC1): a novel therapeutic target in patients with rheumatoid arthritis. (12th June 2018) - Göschl, L.; Mueller, L.; Saferding, V.; Knapp, S.; Backlund, J.; Scheinecker, C.; Smolen, J.; Ellmeier, W.; Steiner, G.; Bonelli, M.
Abstract : Background: Despite enormous efforts to develop new therapeutic strategies for treatment of rheumatoid arthritis (RA), the large number of non responding patients to currently available drugs underlies the unmet need to identify new therapeutic targets. Objectives: Certain CD4 + T cell subsets, especially Th17 cells, have been shown to be major drivers of inflammation in patients with RA. The expression of their key transcription factors is controlled by histone modifications which includes acetylation of lysine residues mediated by histone deacetylases (HDAC). Indeed, pan HDAC inhibitors have been shown to be a potential therapeutic strategy. However, major side effects limited the clinical use and underline the need of more specific HDAC inhibitors. We therefore addressed the individual role of HDAC1 on the development of collagen-induced arthritis model (CIA). Methods: Mice with a T cell specific deletion of HDAC1 (HDAC1 cKO) were generated by using the CD4Cre/LoxP system. Collagen induced arthritis (CIA) was induced at week 8. Animals were scored for paw swelling and grip strength. After 10 weeks, mice were sacrificed and paraffin sections of the affected joints were analysed for histomorphologic signs of inflammation, cartilage and bone destruction. Anti-CII antibody levels were determined by ELISA. Serum samples were analysed for various cytokines by multiplex assays. CCR6 expression in CD4 T cells was analysed by flow cytometry. Results: To address potential effects of HDAC1 in the pathogenesis of RA, CIA was induced in HDAC1cKO mice and WT mice. Surprisingly HDAC1cKO mice were completely protected from the development of arthritis. In line with the clinical data, histological analysis revealed no signs of inflammation, no bone erosion and no osteoclasts in the joints of HDAC1cKO mice. Anti-CII antibodies, including total IgG and igG2c were detected in HDAC1cKO and WT mice. Surprisingly, IL-17 was significantly decreased in the serum of HDAC1 cKO mice as compared to WT mice, suggesting a role of HDAC1 in the development of Th17 cells. To see whether HDAC1 is involved in the regulation of the chemokine receptor 6 (CCR6), the main marker of Th17 cells, we compared the upregulation of CCR6 in CD4 + T cells from WT and HDAC1cKO mice. Indeed, CCR6 could not be upregulated in CD4 + T cells from HDAC1cKO mice upon IL-6 in vitro . These data support the role of HDAC1 in the regulation of CCR6, an important chemokine receptor, which is necessary for the migration of pathogenic Th17 cells and therefore for the development of arthritis. Conclusions: Our data show the importance of HDAC1 as a key immune regulator in the pathogenesis of T cell driven collagen induced arthritis. Therefore, it might be considered as an interesting novel therapeutic target in RA. Disclosure of Interest: None declared